Facilities of renewal of functions to ligamentous muscular systems of man after the physical loadings - Sikura A.Y (Kharkov National Pedagogical University, 2010)
The problem of the state of health of young people and their physical development is examined. The initial indexes of free motions and influence of loading are probed on their changes. The proportion of development of body of man is rotined. Rehabilitation facilities are considered for a return to the initial indexes of proportion of development of body of man. The method of rapid renewal of deep short muscles of man, which substantially hindered the process of weakening is offered. Application of method is improved by the general state of health, harmonizes a feel.